2021
DOI: 10.3399/bjgpo.2021.0182
|View full text |Cite|
|
Sign up to set email alerts
|

GP perceptions of telehealth services in Australia: a qualitative study

Abstract: BackgroundPrimary care providers have been rapidly transitioning from in-person to telehealth care during the 2019 coronavirus (COVID-19) pandemic. There is an opportunity for new research in a rapidly evolving area, where evidence for telehealth services in primary care in the Australian setting remains limited.AimTo explore general practitioner (GP) perceptions on providing telehealth (telephone and videoconsultation) services in primary care in Australia.Design & settingA qualitative study using semi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
0
20

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(123 citation statements)
references
References 35 publications
2
101
0
20
Order By: Relevance
“…Many clinicians and health services have continuously expressed the need for funding to provide telehealth services, particularly within the primary care sector. 11,12,18 These study findings further support that additional telehealth funding was important from a GP perspective. This was demonstrated through the significant provision of GP telehealth consultations after the first policy change.…”
Section: Importance Of Funding For Telehealth Uptake and Provisionsupporting
confidence: 64%
See 2 more Smart Citations
“…Many clinicians and health services have continuously expressed the need for funding to provide telehealth services, particularly within the primary care sector. 11,12,18 These study findings further support that additional telehealth funding was important from a GP perspective. This was demonstrated through the significant provision of GP telehealth consultations after the first policy change.…”
Section: Importance Of Funding For Telehealth Uptake and Provisionsupporting
confidence: 64%
“…The high use of telephone over videoconference by GPs has been influenced by many factors such as the perception that sufficient quality care can be provided by telephone, consumer demand, and financial considerations in general practice settings. 11,12 However, GP services are also impacted by the complex interdependencies of local practice needs, organisational levels, and government policies. 11,13 This means that GP services are heavily affected by policy changes implemented at a federal level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 This trend has been qualitatively explored where it was reported that clinicians found the telephone easier to initiate than videoconferencing. 13,17 A study exploring the effect in outpatient pharmacist clinics during the pandemic found that even when videoconference consultations were reimbursed at a higher rate for the organisation, clinician willingness played a major role in modality choice with telephone staying predominant. 13 However, psychiatrists and psychologists used a higher proportion of videoconference than the telephone, with the exception of psychiatrist review consultations.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Nevertheless, there is a paucity of evidence in this field, reflecting low levels of VC usage in primary care to date. 5 , 23 , 25 …”
Section: Introductionmentioning
confidence: 99%